Local Media in the Power Vortex of PIK 2: A Hierarchy of Influences Analysis - Tusnedi; Ail Muldi; Mia Dwianna Widyaningtyas (Journal of Humanities and Social Sciences Studies, 2026)
The development of Pantai Indah Kapuk 2 (PIK 2) on the northern coast of Banten as a National Strategic Project (PSN) has generated various social and environmental concerns, particularly among traditional fishing communities. In this context, local media serve as an important space for articulating public grievances, aspirations, and interests. This study critically examines the news production process surrounding the PIK 2 megaproject in two local newspapers, Banten Pos and Radar Banten, using the Hierarchy of Influences (HoI) framework. This study adopts a critical paradigm with a qualitative approach and a case study design. Data were collected through in-depth interviews with five informants consisting of editors-in-chief/media leaders, editors, and journalists. In addition, document analysis of PIK 2 news archives published between 2020 and 2024 was used as supporting data. The collected data were analyzed thematically based on the five levels of the HoI framework. Data trustworthiness was strengthened through source triangulation and methodological triangulation. The findings show that, at the individual level, journalists’ professional experience, along with their geographical and social proximity to coastal issues, strengthened their sensitivity in reporting. At the media routines level, there was a constant negotiation between the demand for rapid daily news production and the need for more in-depth investigative reporting. At the organizational level, gatekeeping was carried out rigorously to anticipate legal risks and potential social tensions. At the extra-media level, external pressure did not appear in the form of overt censorship, but operated through soft pressure that encouraged newsrooms to exercise greater caution in assessing reporting risks. At the ideological level, local media had to engage with a developmentalist discourse that emphasized investment and economic growth. Nevertheless, Banten Pos and Radar Banten continued to provide space for the voices of fishermen and affected coastal communities. This study concludes that local journalistic practices in Banten are shaped by the tension between professional idealism, the media’s social control function, and strong structural constraints rooted in local economic and political relations.